Design and Implementation of a Multiple Load Controlling Device Using Voice Command Sensor (GUB Journal of Science and Engineering, 2018)
The living standard of modern society has significantly changed by the rapid growth of Technology. The development of automated load control device is becoming more popular of the home system. At present the available automated load controlling devices in the market have several drawbacks with high operating costs incompatible standards. In this work a wireless automatic load controlling device is developed based on microcontroller and cellular phone to operate different home appliances such as television, light, fan, and air conditioner by voice command. The device is user-friendly and comparatively cost-effective. The simulation is done by using Proteus 8 professional software. Finally, an experimental setup is developed and tested result shows that the device is working properly.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 60-64